Correlation between roundhouse kick and countermovement jump performance - de O Goulart, K. N.; Corgosinho, R. F.; Rodrigues, S. A.; Drummond, M. D. M.; Flor, C. A. G.; Goncalves, R.; Szmuchrowski, L. A.; Couto, B. P. (Archives of Budo, 2016)
Background and Study Aim: Taekwondo (TKD) is a combat sport in which leg techniques are predominant. Roundhouse (bandal chagi) is one of the kicking techniques commonly used in competition. Evaluate and monitoring the power and accuracy of each blow is crucial for training process. Sports scientists and coaches have used the countermovement jump to evaluate the strength and power of lower limbs muscles. However, it is not a specific taekwondo test. Therefore, it was interesting to compare kick and jump performance in order to show the importance of monitoring training by specifics tests. The purpose of this study was to correlate the countermovement jump performance with the roundhouse kick performance in TKD athletes. It was hypothesized that there will not be an elevated correlation between them.